Effect of Models Problem Based Learning with Approach Problem Posing on The Mathematical Analytical Abilities of Junior High School Students - Ustifa, Dina; Adi, Eka Pramono; Kurniawan, Citra (Proceedings Series of Educational Studies, 2024)
In learning mathematics, it always contains numeracy skills as well as analytical skills related to solving problems in everyday life. Application of learning models Problem Based Learning with approach Problem Posing aims to improve students' analytical skills so that they gain new knowledge to solve problems. This research uses quantitative methods quasi experiment with type pretest posttest control group design. To find out the effect of implementing this model, namely through a test instrument in the form of a written test or essay which is used to measure analytical abilities according to analytical ability indicators. The research results state that the implementation Problem Based Learning with approach Problem Posing has a significant influence on students' analytical abilities in mathematical numeracy. It is hoped that future researchers will be able to apply research regarding the model Problem Based Learning with approach Problem Posing over a longer research period. Keywords: Problem Based Learnin